Combined metabolome and transcriptome analysis revealed that MSTN regulated the process of bovine fatty acid metabolism in gut - Gao, Li; Ma, Yong; Wang, Lili; Wu, Hao; Kang, Ruobing; Li, Guangpeng; Yang, Lei; Wen, Tong (Frontiers in Veterinary Science, 2025)
IntroductionMSTN is a well-studied inhibitor of skeletal muscle development, but its mechanism of affecting gut metabolites and the functions it exerts through this pathway are still unclear. This study aims to reveal how MSTN affects the metabolism process by regulating gut metabolites.MethodsCombined analysis of jejunal contents metabolome and jejunal tissue transcriptome was used to compare the differences in intestinal metabolites and intestinal tissue gene expression between MSTN mutant and wild-type bovines.ResultsMetabolomic analysis identified that compared to wild-type bovine, the abundance of 304 metabolites were significantly changed in MSTN mutant cattle including 142 upregulated and 162 downregulated. Transcriptome results showed that the expression level of 1541 genes were influenced by MSTN disruption, including 536 upregulated genes and 1005 downregulated genes, which were categorized into 311 KEGG signaling pathways, primarily related to disease and metabolism. Correlation analysis results suggested a notable cross-regulation between the transcript levels of some specific genes in jejunal tissues and the abundance of jejunal metabolites, represented by fatty metabolites and genes associated with fatty acid degradation, synthesis and elongation.DiscussionCollectively, the result of this study indicated that MSTN gene mutation led to alterations in gut microbial metabolites by increasing the abundance of beneficial monounsaturated fatty acids (MUFAs) such as oleic acid, then to promote fatty acid degradation while inhibiting its synthesis by regulating the expression levels of relevant genes. These results provide a foundation for understanding the effects of MSTN gene mutations on gut metabolites and its certain functions that MSTN regulated via gut metabolites